2013
DOI: 10.1074/mcp.m113.030379
|View full text |Cite
|
Sign up to set email alerts
|

Grading Breast Cancer Tissues Using Molecular Portraits

Abstract: Tumor progression and prognosis in breast cancer patients are difficult to assess using current clinical and laboratory parameters, where a pathological grading is indicative of tumor aggressiveness. This grading is based on assessments of nuclear grade, tubule formation, and mitotic rate. We report here the first protein signatures associated with histological grades of breast cancer, determined using a novel affinity proteomics approach. We profiled 52 breast cancer tissue samples by combining nine antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…This work indicated a candidate 49-plex protein signature [24], refined and extended to a tentative 21-plex peptide signature (Olsson et al, submitted), for discriminating between histological grade 1,2 and 3 classified breast cancer, and for outlining the heterogeneity among grade 2 tumors. Importantly, these candidate biomarker signatures are completely different from the biomarker panels presented in this study, but they were found to provide similar biological information.…”
Section: Discussionmentioning
confidence: 99%
“…This work indicated a candidate 49-plex protein signature [24], refined and extended to a tentative 21-plex peptide signature (Olsson et al, submitted), for discriminating between histological grade 1,2 and 3 classified breast cancer, and for outlining the heterogeneity among grade 2 tumors. Importantly, these candidate biomarker signatures are completely different from the biomarker panels presented in this study, but they were found to provide similar biological information.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proteomics has emerged as an integral part of modern biomedicine. For example, proteomics tools have been used for both cancer diagnosis and therapy selection as well as for researching the underlying mechanisms of disease pathogenesis and progression 1214 . Specifically, one recent proteomic-based breast cancer study uncovered clinically distinct protein signatures for different histologically graded tumors 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, proteomics tools have been used for both cancer diagnosis and therapy selection as well as for researching the underlying mechanisms of disease pathogenesis and progression 1214 . Specifically, one recent proteomic-based breast cancer study uncovered clinically distinct protein signatures for different histologically graded tumors 12 . Another study developed a triple-negative breast cancer-specific protein profile 13 and a study by Tyanova et al characterised functional differences between different breast cancer subtypes 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These patients are mostly diagnosed with node positive disease, larger tumor size (T3/T4), undifferentiated tumor grade 3 (70%), minimal level of hormone receptor positivity, and overall poorer prognosis and survival . Prognosis prediction and treatment decision depend on the conventional histopathological tests, which often fail for discrimination of risk group and early diagnosis …”
Section: Introductionmentioning
confidence: 99%